Study of Authority from a Civil Law Perspective - Ayu Vijaya Laksmi, Dyah (Lafadz Jaya Publisher, 2025)
The concept of authority plays a pivotal role in the context of civil law, particularly in delineating the powers and responsibilities vested in legal subjects through statutory provisions. This research explores the nuanced distinctions between